The Pros and Cons of Adopting Technology as a Business Pilot: Global Perspective - Selase, Afenya Millicent; Selase, Aphu Elvis (Indian Journal of Finance and Banking, 2019)
Technology has revolutionized human society. A complex scientific knowledge that takes various forms is technology. It is also referred to as a set of meticulous knowledge used to create tools process actions and extricate materials to make work easy. Technology includes equipment such as computers, mobile phones, multimedia, software, games and apps, these are simple tools individuals use in their daily lives to make life comfortable and luxurious. Technology comes in various forms of such as mechanical, electrical, industrial or manufacturing and medical technology.   Any establishment set as a going concern for profit maximization is a business. Technology has various benefits which helps businesses achieve its ultimate goal, thus, maximize profit. Technological infrastructure’s impact on business efficiency and effectiveness is inevitable. There is a correlation between technology and business profit maximization be it positive or negative, because it has various impacts on businesses. The question is, does the type of technology adopted affect the business? The various types of technology indicate it has different purpose, to be efficient it needs to be used effectively. Today’s business world has been massively influenced by internet technology adoption. The utilization among business is inescapable since technology is rapidly regenerating global production, work and business methods, trade and consumption patterns of enterprises and consumers therefore, the paper is to evaluate if there is the need to adopt a particular technology that best fit a business industry.